Study on the Effect of Grinding Fineness on Flotation in Maoniuping Rare Earth Mine - Jianxin XU; Zhu WU (Kuangchan zonghe liyong, 2025)
Maoniuping rare earth mine in Sichuan Province is the second largest rare earth one in China. It is rich in rare earth resources, and there are a lot of fluorite and barite resources associated with it. Due to the different distribution size and grinding difficulty of the three minerals of rare earth, barite and fluorite in the ore, the flotation test of grinding fineness of the ore was carried out in order to maximize the comprehensive utilization of useful minerals. The results show when the grinding fineness is controlled at -0.074 mm 53.47%, the comprehensive recovery rate of all useful minerals is relatively high, and the comprehensive utilization of co-associated resources is realized.